GAYA HIDUP HEDONISME MAHASISWA DI KOTA PEKANBARU - Yulia Rista; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this study is to: (1) To find out the driving factors of students with hedonism, (2) To identify the socioeconomic background of parents of students who are concerned with hedonism. This research uses qualitative methods. The subject of this research is a student of Management of the Faculty of Social and Political Sciences, Universitas Riau. The data is taken by way of in-depth interviews. The results showed that: (1) The pattern of student hedonism in Pekanbaru as well as shopping for branded goods at a high price for high satisfaction and confidence. Hanging out and spending time on the mall with friends for hours by showing off advanced gadgets is phenomenal culture among students who are many in instagram photos. (2) The effect of the pattern of student hedonism in Pekanbaru is consumptive behavior that is to spend money to buy goods without seeing the value of the using, but the goods are purchased only for pleasure only without the need. This seems extravagant because it wastes money to buy various things that are not important, just to show off the brand / expensive goods. An instant mentality that teaches youth not to want to go through a convoluted process of confronting a happiness. (3) The motivation of students in Pekanbaru in the application of hedonism is in terms of weekend and recreation. According to them spending time shopping branded goods, watching movies, and hanging out in cafes is the main reason for the application of hedonism behavior among students. They feel weekend and recreation is one of the most important activities in the mindset of various busyness. They feel more happy after the walk and spend time in the mall with friends. Keyword : hedonism lifestyle, brand, and student